The Sounds of Silence: Perspectives on Documenting Acoustic Landscapes at the Intersection of Remoteness, Conservation and Tourism - Jonathan Carruthers-Jones; George Holmes; Roger Norum (Humanities)
The humanities are often criticised for lacking a way through from the complexity they reveal to the challenges they might hope to address. In the face of the accelerating biodiversity crisis, we present two projects that aim to respond to the limitations and lack of interdisciplinary conversations in conservation and in humanities research. At field sites in Finnish Lapland and the French Pyrenees, we document how conservation humanities research can be used to develop a more pragmatic and integrated transdisciplinary approach to conservation in remote and fragile landscapes. Firstly, we show how sound and soundscapes are important subjects of study in both conservation biology and the humanities. We also highlight their importance to conservation planners and policy makers seeking to preserve biodiversity and landscape characteristics, as well as our social values thereof, which, together, are critical to their survival. Secondly, we demonstrate how integrated conservation humanities methods can lead to rich local-level insights on key conservation themes that can then be scaled via existing large-scale acoustic monitoring and spatial datasets to support decision making across much larger areas. Finally, we highlight how the participatory mapping approach at the core of our integrated methodology shows potential to generate change in the real world and meet the classic operationalisation challenge that academia faces.